Patient Safety Determinants in Surgical Settings: A Literature Review - Satriyanto, Muhammad Dwi; Sayidah, Nur; Utami Ady, Sri (Dinasti Publisher, 2024)
This research highlights the importance of patient safety in surgical procedures and the influencing factors. Patient safety becomes the primary focus, particularly within the scope of the operating room. Several crucial factors that contribute to maintaining patient safety include the operating room environment, staff participation, safety protocols, and communication among surgical team members. Nineteen journals have been analyzed by the researcher to identify determinants of patient safety within the surgical operating room. The analysis results from this literature review reveal that factors such as safety culture, effective communication among surgical teams, and the physical conditions of the operating room significantly impact patient safety. The significance of medical team skills, implementation of safety protocols, and the use of checklists have proven to reduce the risk of errors in surgical procedures. Conversely, occurrences of surgical wound infections, medical equipment failures, and lack of communication among medical teams can jeopardize patient safety.